Super-twisting sliding mode controllers based on D-PSO optimization for temperature control of an induction cooking system - Abdeldjalil Abdelkader Mekki; Abdelkader Kansab; Mohamed Matallah; Zinelaabidine Boudjema; Mouloud Feliachi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this study, we perform the control of the temperature evolution versus time of induction cooking system using a super twisting sliding mode control (STSMC) based on Dynamic Particle Swarm Optimization (D-PSO). First, we will determine the evolution of the temperature in the middle of the pan bottom using the FEM method. The found temperature exceeds the limit of the desired cooking temperature (150-200°C). Second, to limit temperature increase, a (ST-SMC) method combined with a (D-PSO) algorithm is used to get the desired temperature. Particles Swarm Optimization (D-PSO) method is used to optimize the parameters of the gain of (ST-SMC) and improve its performance. The simulation results show that the use of the optimized super twisting sliding mode controller helps to achieve a desired value of cooking.